The Lifework of a Labor Historian: Essays in Honor of Marcel van der Linden - Bosma, Ulbe; Hofmeester, Karin (Studies in Global Social History, 2018)
The Life Work of a Labor Historian: Essays in honor of Marcel van der Linden, presents the latest developments in the global history of labor, work and workers, and of capitalism and its critics. Readership: All interested in (global) history of labor, including all types of work and workers free and unfree and labour protest as well as anyone concerned with the history Marxism and capitalism and its critics.